2017
DOI: 10.1038/srep46053
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic representation of time in brain states

Abstract: The ability to process time on the scale of milliseconds and seconds is essential for behaviour. A growing number of studies have started to focus on brain dynamics as a mechanism for temporal encoding. Although there is growing evidence in favour of this view from computational and in vitro studies, there is still a lack of results from experiments in humans. We show that high-dimensional brain states revealed by multivariate pattern analysis of human EEG are correlated to temporal judgements. First, we show … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In a previous study, we have already shown that using multivariate pattern analysis on the EEG signal can reveal activity related to temporal processing (Bueno et al, 2017). However, in that experiment, MVPA was applied while participants performed a temporal categorisation task in which they had to judge whether a certain duration was shorter, equal or longer than a reference.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study, we have already shown that using multivariate pattern analysis on the EEG signal can reveal activity related to temporal processing (Bueno et al, 2017). However, in that experiment, MVPA was applied while participants performed a temporal categorisation task in which they had to judge whether a certain duration was shorter, equal or longer than a reference.…”
Section: Discussionmentioning
confidence: 99%
“…However, in that experiment, MVPA was applied while participants performed a temporal categorisation task in which they had to judge whether a certain duration was shorter, equal or longer than a reference. Thus, it was possible that the pattern analysis was picking up activity related to decisional processing or to particular strategies adopted by the participants (Bueno et al, 2017). Similarly, a study that also investigated whether the pattern of EEG activity during temporal judgements was consistent across vision and audition focused its analysis during the interval to be judged (N'Diaye et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this view, neural systems can benefit from the temporal evolution of their states, caused by the variation in neural and synaptic properties. The overall effect results in an adaptation of cerebral networks that could be tuned to discriminate temporal intervals (Bueno et al, 2017 ). State-dependent models can be extended to be consistent with the majority of timing models (Hass and Durstewitz, 2016 ), with the different models indicating specific constraints on what would collapse the state space.…”
Section: The Viewmentioning
confidence: 99%